PENGEMBANGAN SISTEM PAKAR BERBASIS WEB MOBILE UNTUK MENGIDENTIFIKASI PENYEBAB KERUSAKAN TELEPON SELULER DENGAN MENGGUNAKAN METODE FORWARD DAN BACKWARD CHAINING - Wamiliana Wamiliana; Aristoteles Aristoteles; Depriyanto Depriyanto (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2013)
Phone cell users are now countless, but many of them are not able to solve the problem if there are damages to their phones. This paper discusses about the development of expert system that can assist to identify those damages. This system uses forward chaining and backward chaining methods which are known as the searching techniques in getting a conclusion of the existing problem, and this system is built by using PHP programming language and MySQL as the database, and it can only be accessed by using a mobile browser.